Fluorescent nucleic acid gel strong adhesive and preparation method thereof
By combining tetrastyrene molecules with double-stranded DNA, a strong adhesive for fluorescent nucleic acid gel was formed, which solved the mechanical and mechanical properties and detection problems of DNA materials, achieved high-strength bonding and visualization, and expanded the Its application in the field of biomedical science.
Patent Information
- Application Number
- CN202411391824.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-07
AI Technical Summary
The mechanical and mechanical properties and adhesive properties of existing DNA gel materials are weak and difficult to detect and track, which limits their application in the field of biomedical science.
The tetrastyrene molecules are combined with double-stranded deoxyribonucleic acid to form an ionic complex through electrostatic action, and a fluorescent nucleic acid gel strong adhesive is prepared, which has high-intensity mechanical properties and fluorescent properties.
It realizes high-strength adhesive properties and easy-to-detection fluorescent nucleic acid gel materials, has good biocompatibility and visualization advantages, and expands the application of DNA in the field of biomedical science.
Smart Images

Figure HDA0005072636220000011 
Figure HDA0005072636220000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomaterials and aggregation-induced luminescence materials, and mainly relates to a fluorescent nucleic acid gel strong adhesive and a preparation method thereof. Background Art
[0002] In the fields of materials science and biomedicine, DNA is one of the important biomaterials. With its double helix structure, hydroxyl groups and negative charges, DNA can be modified with covalent bonds, electrostatically bonded to ionic compounds, and other methods to achieve diversified functions. Among DNA materials, gel materials, as a soft material, have good editability and stimulus responsiveness, can well meet many requirements of medical materials, and have good application prospects.
[0003] Compared with chemical adhesives, DNA adhesives have obvious advantages in terms of toxicity, environmental friendliness and renewability. Their good biocompatibility and degradability can provide better bonding treatment for biological tissues. However, in reported studies, DNA gel materials usually show weak mechanical properties and bonding properties. At the same time, since the DNA molecules themselves do not contain fluorescent groups, DNA adhesive materials will also be difficult to detect and track during the application process, which brings difficulties to the detection of adhesive residues of this type of adhesive materials after the treatment. So far, there has been no report on strong DNA gel adhesive materials with easy detection and tracking properties.
[0004] Tetraphenylethylene molecules have aggregation-induced emission properties and can be excited by ultraviolet light in a solvent-free or gel state to produce bright fluorescence visible to the naked eye. Combining with biological molecules can make the prepared biofunctional materials have the advantage of visualization. Aggregation between tetraphenylethylene groups can also generate intermolecular forces, which can be used to improve the mechanical properties of the material at the same time. With the help of the above two properties, tetraphenylethylene molecules are combined with deoxyribonucleic acid molecules to prepare bioadhesive materials with both high-strength mechanical properties and fluorescent properties. However, there have been no reports on the use of tetraphenylethylene molecules to prepare fluorescent deoxyribonucleic acid-based strong adhesive materials, which limits the development of deoxyribonucleic acid in the fields of visualized strong biomaterials and bioadhesive therapy. Therefore, the development of fluorescent nucleic acid gel strong adhesive materials is of great significance for expanding the application of deoxyribonucleic acid materials in basic scientific research and biomedical fields. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a fluorescent nucleic acid gel strong adhesive and a preparation method thereof.
[0006] The technical solution of the present invention is as follows:
[0007] The invention provides a fluorescent nucleic acid gel strong adhesive, the preparation raw materials of which include double-stranded deoxyribonucleic acid, a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure and dimethyl sulfoxide.
[0008] In the present invention, the number of base pairs of the double-stranded deoxyribonucleic acid is 2000.
[0009] In the present invention, the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure is 8,8'-((1,2-diphenylethylene)-bis-4-phenoxy)bis(N,N,N-trimethyloctyl)ammonium bromide.
[0010] In the present invention, the preparation method of the fluorescent nucleic acid gel strong adhesive comprises:
[0011] Under room temperature conditions, an aqueous solution of double-stranded deoxyribonucleic acid is mixed with an aqueous solution of a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure, the obtained mixed solution is shaken and centrifuged, and the supernatant is discarded, and the remaining precipitate product is washed with water and then freeze-dried to obtain a solid ion complex material of double-stranded deoxyribonucleic acid and the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure, and dimethyl sulfoxide is added to the obtained solid ion complex material of double-stranded deoxyribonucleic acid and the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure to obtain a fluorescent nucleic acid gel strong adhesive.
[0012] In the present invention, in the preparation method of the fluorescent nucleic acid gel strong adhesive, the mass concentration of the double-stranded deoxyribonucleic acid aqueous solution is 10.0 mg / mL, and the concentration of the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure is 10.0-15.0 mmol / L.
[0013] In the present invention, in the preparation method of the fluorescent nucleic acid gel strong adhesive, in the mixed solution, the molar ratio of the double-stranded deoxyribonucleic acid to the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure is 1:1 to 1:2 in terms of the number of bases.
[0014] In the present invention, in the preparation method of the fluorescent nucleic acid gel strong adhesive, the mixed solution is shaken for 3 to 5 minutes, and the precipitate product is freeze-dried for 10 to 12 hours.
[0015] In the present invention, in the preparation method of the fluorescent nucleic acid gel strong adhesive, dimethyl sulfoxide is added to the solid ion complex material of the obtained double-stranded deoxyribonucleic acid and the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure, and the amount of dimethyl sulfoxide added is 50% of the mass of the solid ion complex material of the obtained double-stranded deoxyribonucleic acid and the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure.
[0016] The present invention provides a fluorescent nucleic acid gel strong adhesive and a preparation method thereof, wherein the fluorescent nucleic acid gel strong adhesive and the preparation method thereof have the following characteristics:
[0017] 1. The fluorescent nucleic acid gel strong adhesive obtained by the present invention is an organic gel material of an ion complex formed by electrostatic force between double-stranded deoxyribonucleic acid and a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure.
[0018] 2. The fluorescent nucleic acid gel strong adhesive obtained by the present invention can emit an easily observable fluorescence phenomenon under ultraviolet light.
[0019] 3. The fluorescent nucleic acid gel strong adhesive obtained by the present invention can achieve high-strength bonding of a variety of materials, with a maximum bonding strength of 7.58 MPa.
[0020] 4. The fluorescent nucleic acid gel strong adhesive obtained by the present invention has good biocompatibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a fluorescence spectrum of the fluorescent nucleic acid gel strong adhesive described in Example 1 under ultraviolet light excitation with a wavelength of 365nm.
[0022] Figure 2 This is a tensile test graph of the bonding strength of the fluorescent nucleic acid gel strong adhesive described in Example 1 when bonding glass materials. DETAILED DESCRIPTION
[0023] The present invention provides a fluorescent nucleic acid gel strong adhesive and a preparation method thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be pointed out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0024] The present invention will be further described below in conjunction with embodiments:
[0025] Embodiment 1:
[0026] At room temperature, 0.10 mL of an aqueous solution of double-stranded deoxyribonucleic acid (the number of base pairs is 2000) with a concentration of 13.20 mmol / L of an aqueous solution of a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure was mixed in a centrifuge tube, the obtained mixed solution was shaken for 3 minutes, the shaken mixed solution was centrifuged and the supernatant was discarded, and a precipitate was obtained at the bottom of the centrifuge tube. The precipitate was washed and purified, and then freeze-dried for 10 hours to obtain a solid ion complex material of double-stranded deoxyribonucleic acid and a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure. The obtained solid ion complex material was weighed to be 1.2 mg, and 0.6 mg of dimethyl sulfoxide was added to the obtained solid ion complex material to prepare a fluorescent nucleic acid gel strong adhesive.
[0027] The fluorescence spectrum of the prepared fluorescent nucleic acid gel strong adhesive under the excitation of ultraviolet light with a wavelength of 365nm is as follows: Figure 1 As shown, according to Figure 1 , it is concluded that the fluorescent nucleic acid gel strong adhesive can generate a fluorescent signal under ultraviolet light excitation. Under ultraviolet light excitation with a wavelength of 365nm, the fluorescent nucleic acid gel strong adhesive can generate a strong fluorescence phenomenon visible to the naked eye.
[0028] The prepared fluorescent nucleic acid gel strong adhesive uses glass as the bonded material. The bonding strength tensile test graph of the fluorescent nucleic acid gel strong adhesive is as follows: Figure 2 As shown, according to Figure 2 , it is concluded that when the fluorescent nucleic acid gel strong adhesive is used to bond glass materials, the average bonding strength of the fluorescent nucleic acid gel strong adhesive can reach 7.58 MPa.
[0029] The prepared fluorescent nucleic acid gel strong adhesive has been tested and found to be able to adhere to a variety of materials such as plastics, rubber, ceramics, leaves, paper, steel plates, wood, pig skin and the like.
[0030] The prepared fluorescent nucleic acid gel strong adhesive has been tested to have low biological toxicity and good biocompatibility.
[0031] Comparative Example 1:
[0032] At room temperature, 0.10 mL of an aqueous solution of double-stranded deoxyribonucleic acid (the number of base pairs is 2000) with a concentration of 13.20 mmol / L of an aqueous solution of a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure are mixed in a centrifuge tube, the resulting mixed solution is shaken for 3 minutes, the shaken mixed solution is centrifuged and the supernatant is discarded, a precipitate is obtained at the bottom of the centrifuge tube, the precipitate is washed and purified, and then freeze-dried for 10 hours to obtain a solid ion complex material of double-stranded deoxyribonucleic acid and a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure.
[0033] The solid ion composite material of double-stranded deoxyribonucleic acid and double-headed quaternary ammonium salt surfactant containing tetraphenylethylene structure prepared in Comparative Example 1 was tested to have no adhesion property to glass materials.
[0034] Comparative Example 2:
[0035] At room temperature, 0.10 mL of an aqueous solution of double-stranded deoxyribonucleic acid (the number of base pairs is 2000) with a 0.25 mL of an aqueous solution of a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure with a concentration of 13.20 mmol / L are mixed in a centrifuge tube, the obtained mixed solution is shaken for 3 minutes, the shaken mixed solution is centrifuged and the supernatant is discarded, and a precipitate is obtained at the bottom of the centrifuge tube. The precipitate is washed and purified, and then freeze-dried for 10 hours to obtain a solid ion complex material of double-stranded deoxyribonucleic acid and a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure. The obtained solid ion complex material is weighed to be 1.2 mg, and 1.2 mg of dimethyl sulfoxide is added to the obtained solid ion complex material to obtain a fluorescent nucleic acid gel material.
[0036] The fluorescent nucleic acid gel material prepared in Comparative Example 2 was tested to have an adhesion strength of 20 KPa to glass material.
[0037] Comparative Example 3:
[0038] At room temperature, 38 μL of an aqueous solution of double-stranded deoxyribonucleic acid (the number of base pairs is 22) with a 0.25 mL aqueous solution of a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure with a concentration of 13.20 mmol / L were mixed in a centrifuge tube, the obtained mixed solution was shaken for 3 minutes, the shaken mixed solution was centrifuged and the supernatant was discarded, and a precipitate was obtained at the bottom of the centrifuge tube. The precipitate was washed and purified, and then freeze-dried for 10 hours to obtain a solid ion complex material of double-stranded deoxyribonucleic acid (the number of base pairs is 22) and a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure. The obtained solid ion complex material was weighed to 1.0 mg, and 0.5 mg of dimethyl sulfoxide was added to the obtained solid ion complex material to obtain a fluorescent nucleic acid gel material.
[0039] The fluorescent nucleic acid gel material prepared in Comparative Example 3 was tested to have an adhesion strength of 0.80 MPa to glass material.
[0040] Comparative Example 4:
[0041] At room temperature, 0.10 mL of an aqueous solution of double-stranded deoxyribonucleic acid (the number of base pairs is 2000) with a 0.25 mL of an aqueous solution of a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure with a concentration of 13.20 mmol / L are mixed in a centrifuge tube, the obtained mixed solution is shaken for 3 minutes, the shaken mixed solution is centrifuged and the supernatant is discarded, and a precipitate is obtained at the bottom of the centrifuge tube. The precipitate is washed and purified, and then freeze-dried for 10 hours to obtain a solid ion complex material of double-stranded deoxyribonucleic acid and a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure. The obtained solid ion complex material is weighed to be 1.2 mg, and 0.6 mg of ethanol is added to the obtained solid ion complex material to obtain a fluorescent nucleic acid gel material.
[0042] The fluorescent nucleic acid gel material prepared in Comparative Example 4 was tested to have an adhesion strength of 0.35 MPa to glass material.
[0043] Comparative Example 5:
[0044] At room temperature, 0.10 mL of an aqueous solution of double-stranded deoxyribonucleic acid (the number of base pairs is 2000) with a concentration of 13.20 mmol / L of an aqueous solution of a single-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure (N,N,N-trimethyl-8-(4-(2-(4-octyloxyphenyl)-1,2-diphenylvinyl)phenoxy)octan-1-ammonium bromide) were mixed in a centrifuge tube, the obtained mixture was shaken for 3 minutes, the shaken mixture was centrifuged and the supernatant was discarded, and a precipitate was obtained at the bottom of the centrifuge tube. The precipitate was washed and purified, and then freeze-dried for 10 hours to obtain a solid ion complex material of double-stranded deoxyribonucleic acid and a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure. The obtained solid ion complex material was weighed to be 0.8 mg, and 0.4 mg of dimethyl sulfoxide was added to the obtained solid ion complex material to obtain a fluorescent nucleic acid gel material.
[0045] The fluorescent nucleic acid gel material prepared in Comparative Example 5 was tested to have an adhesion strength to glass material of 0.39 MPa.
[0046] The above are only preferred embodiments of the present invention. It should be pointed out that those skilled in the art can make several improvements without departing from the principles of the present invention. These improvements should also be regarded as within the protection scope of the present invention.
Claims
1. A fluorescent nucleic acid gel strong adhesive, characterized in that: The synthetic raw materials include double-stranded deoxyribonucleic acid, a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure and dimethyl sulfoxide. The double-stranded deoxyribonucleic acid has 2000 base pairs, and the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure is 8,8'-((1,2-diphenylethylene)-bis-4-phenoxy)bis(N,N,N-trimethyloctyl)ammonium bromide.
2. The method for preparing the fluorescent nucleic acid gel strong adhesive according to claim 1, characterized in that: include: Under room temperature conditions, an aqueous solution of double-stranded deoxyribonucleic acid is mixed with an aqueous solution of a double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure, the obtained mixed solution is shaken and centrifuged, and the supernatant is discarded, and the remaining precipitate product is washed with water and then freeze-dried to obtain a solid ion complex material of double-stranded deoxyribonucleic acid and the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure, and dimethyl sulfoxide is added to the obtained solid ion complex material of double-stranded deoxyribonucleic acid and the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure to obtain a fluorescent nucleic acid gel strong adhesive.
3. The method for preparing the fluorescent nucleic acid gel strong adhesive according to claim 2, characterized in that: The mass concentration of the double-stranded deoxyribonucleic acid aqueous solution is 10.0 mg / mL, and the concentration of the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure is 10.0-15.0 mmol / L.
4. The method for preparing the fluorescent nucleic acid gel strong adhesive according to claim 2, characterized in that: In the mixed solution, the molar ratio of the double-stranded deoxyribonucleic acid to the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure is 1:1 to 1:2, calculated by the number of bases.
5. The method for preparing the fluorescent nucleic acid gel strong adhesive according to claim 2, characterized in that: The mixed solution is shaken for 3 to 5 minutes, and the precipitate product is freeze-dried for 10 to 12 hours.
6. The method for preparing the fluorescent nucleic acid gel strong adhesive according to claim 2, characterized in that: The method comprises adding dimethyl sulfoxide to the solid ion complex material of the double-stranded deoxyribonucleic acid and the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure, wherein the amount of the added dimethyl sulfoxide is 50% of the mass of the solid ion complex material of the double-stranded deoxyribonucleic acid and the double-headed quaternary ammonium salt surfactant containing a tetraphenylethylene structure.
Citation Information
Cited By
Fluorescent carbon dot-nucleic acid adhesive based on liquid-liquid phase separation as well as preparation method and application of fluorescent carbon dot-nucleic acid adhesive
CN121003724A